Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, P. K. (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of α and β-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of β-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of α and β-NiMoO4 at a base pressure of ∼1 × 10−8 mbar. The obtained turn-on field at emission current density of 1 μA/cm2 for β-NiMoO4 nanosheets and α −NiMoO4 is 1.3 V/μm and 2.2 V/μm respectively were observed. The maximum field emission current density of 1.006 mA/cm2at an applied electric field of 2.7 V/μm was achieved for β-NiMoO4 nanosheets. Furthermore, we found that the β-NiMoO4 nanosheets possess good field emission performance compared to α-NiMoO4. The results indicate that NiMoO4can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase.
Keywords: Current stability; field emission; nanosheets; NiMoO4